Managing pandemic crises in shipping: Experience and lessons - Đergović Dragana D.; Kukobat Irena L.; Kukobat Lazo M. (Tehnika)
The paper analyses different aspects of management response to pandemic crises in shipping, as a part of global effort to find the best practice for ensuring health and safe social and working behavior. The main objective was to explore the interconnected challenge of how to balance between carrying out global logistics and maintaining the health of shipping personnel. The methodology involved a detailed examination of the currently available regulations and existing research studies. Through qualitative descriptive analysis of dataset, the paper offers insights into risks and challenges in managing the pandemic's needs, highlights topics specific to corresponding risks in shipping, and gives evaluation of applied risk-mitigation measures. In the context of COVID-19 infection, empirical results revealed that the implications of the pandemic were widespread, but that maritime supply chains had largely adapted to the new conditions using comprehensive emergency-response mechanism. Key findings in this paper underscore significant progress in the shipping industry's approach, so that crisis management may be characterized as prompt and effective. The pandemic's legacy, as well as the recommendations for further improvements, are presented in conclusions. The paper also identify a need for long-term considerations for sustainable development of the maritime sector in the post-pandemic world.